Output and Employment Input-Output Multipliers on the basis of Use and Make Matrices - Thijs Ten Raa; José Manuel Rueda-Cantuche (European Regional Science Association (ERSA), 2005)
In the literature, the construction of technical coefficients is linked to flow data (use and make matrices), but stochastics are imposed on the coefficients when multipliers are calculated, by means of the Leontief inverse. Due the nonlinearity of this operation, the multiplier estimates are biased (it is generally argued that the Leontief inverse underestimates input-output multipliers). By going back to the flow data, this paper provides unbiased and consistent employment and output multipliers input-output estimates for the Andalusian economy. Rectangular use and make matrices are accommodated and technical coefficients, the Leontief inverse, and associated problems (such as negative coefficients) are circumvented.
Keywords: 330